Public perception on the factors contribute to juvenile delinquency: a case study at urban transformation centre (UTC), Melaka Tengah / Zulika Zayid and Nur Faizatul Akma Fauzi - Zayid, Zulika; Fauzi, Nur Faizatul Akma (Faculty of Administrative Science and Policy Studies, 2014)
The purpose of this research is to identify the factors that contribute to public perception on juvenile delinquency at Urban Transformation Centre, Melaka Tengah. This study is to identify whether there is a relationship between the several factors which affecting public perception on juvenile delinquency. The factors are comprises of the family, socioeconomic class and educational experience factors. For this study, the researcher used the convenient sampling as the sampling technique through the questionnaire, 361 respondents were chosen. Various method and analysis are used to analyze the data gathered from the questionnaire. The methods used including descriptive statistical analysis, reliability test, Spearman’s Rank Order Correlation, and Multiple Regression analysis. The result of correlation test shows that all the three factors affect public perception on juvenile delinquency and the final results revealed, among the three (3) factors there is positive relationship between the factors and public perception on juvenile delinquency. Meanwhile, educational experience was found as the most significant factor that affects the public perception on juvenile delinquency by using regression method.